Chemosynthetic homologues of Mycoplasma pneumoniae β-glycolipid antigens for the diagnosis of mycoplasma infectious diseases. Issue 4 (15th February 2018) - Fukuda, Kazuo; Matsuda, Kazuhiro; Matsuda, Sachie; Kado, Sayaka; Masu, Hyuma; Dohi, Hirofumi; Nishida, Yoshihiro
Graphical abstract: Abstract: Mycoplasma pneumoniae expresses β-glycolipids (β-GGLs) in cytoplasmic membranes, which possess a unique β(1 → 6)-linked disaccharide epitope, which has high potential in biochemical and medicinal applications. In the present study, a series of β-GGLs homologues with different acyl chains (C12, C14, C16, and C18) were prepared from a common precursor. An ELISA assay using an anti-(β-GGLs) monoclonal antibody indicated that the synthetic homologues with long acyl chains had greater diagnostic potential in the order C18 > C16 > C14 > C12. Toward a simultaneous detection of natural glycolipids by mass spectrometry (MS), a deuterium-labeled C16 homologue (β-GGL-C16- d 3 ) was prepared and applied as an internal standard for a high-resolution electrospray ionization MS (ESI-MS) analysis. The ESI-MS analysis was used to identify and quantify acyl homologues (C16/C16, C16/C18, and C18/C18) of β-GGL-C16 in cultured M. pneumoniae. A β-GGLs homologue with a 1, 2-diacetyl group (C2) was also prepared as a "water soluble" glycolipid homologue and characterized by 1 H NMR spectroscopy. We envisage that each of these chemosynthetic homologues will provide promising approaches to solve medical and biological problems associated with mycoplasma infectious diseases (MIDs).